ASPERGILLUS CINSI MANTARLAR VE İNVAZİV ASPERGİLLOZ: MİKOLOJİ, PATOGENEZ, LABORATUVAR TANIMI, ANTİFUNGALLERE DİRENÇ VE DUYARLILIK DENEYLERİ - KANTARCIOĞLU, A. Serda; YÜCEL, Ayhan (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Aspergillus species has become one of the most important airborne pathogen in developed countries, causing a significant increase in fatal pulmonary invazive aspergillosis. In spite of the recent progress in the study of laboratory diagnosis and antifungal treatments invazive aspergillosis tends to occur in immunologically debilitated individuals with an overall mortality of >50% and a mortality approaching 100% in allogenic bone marrow transplant patients. This paper briefly reviews the current state of knowledge regarding Aspergillus species and invazive aspergillosis focusing on the mycology, pathogenesis, laboratory diagnosis, antifungal agents and susceptibility tests.